Impact of Mode of Curriculum on Knowledge and Attitudes of Medical Students towards Health Research - Abdul Haseeb; Muhammad Bilal; M. Ahmed Ansari; Ahmed Raheem; Aleena Khan; Mohammad Hussham Arshad; Vanita Motiani; Muhammad Shahzeb Akhtar (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Equipping students with skills in medical research should be an integral part of medical education systems. This study is designed to gauge the difference in knowledge and attitudes towards health research between two sets of undergraduate medical students; those enrolled in the new Problem Based Learning (PBL) education system versus those of the conventional Lecture Based Learning (LBL) curricula. Materials and Methods: From the 4th and 5th years of medical university students, 90 participants were recruited from the Aga Khan University (PBL group) and Dow University of Health Sciences (LBL group) and were presented with structured and pre-validated questionnaire. Responses obtained for knowledge and attitudes of each group were recorded on a scale and graduated in percentages to be compared statistically for differences to identify the effectiveness of each curriculum. Results: The score on the knowledge scale for the PBL group was found to be 44.77% against the 31.55% of the LBL students (p-value<0.001). Furthermore, the mean attitude score of AKU students was 72.22% as opposed to the 56.11% of the DUHS participants (p-value<0.001). Conclusion: The PBL group achieved significantly higher scores in all aspects than the LBL group, showing healthier attitudes towards health science research along with better knowledge. Hence, the apparent positive influence of PBL curricula on attitudes towards research may be helpful in improving research output of medical students in Pakistan.